2011
DOI: 10.1007/s11745-011-3598-1
|View full text |Cite
|
Sign up to set email alerts
|

Eicosapentaenoic Acid and Docosahexaenoic Acid Regulate Modified LDL Uptake and Macropinocytosis in Human Macrophages

Abstract: There is evidence that long chain n-3 PUFA (such as from fish oils) provide atheroprotection through, in part, changes in macrophage function although it has not been fully determined whether these n-3 PUFA target cellular mechanisms that control macrophage foam cell formation. Therefore, we investigated whether the n-3 PUFA, EPA and DHA, modulate modified low-density lipoprotein (LDL) uptake by human macrophages. The uptake of fluorophore labeled acetylated LDL (AcLDL) and/or oxidized LDL (OxLDL) by THP-1 mac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 52 publications
0
33
1
Order By: Relevance
“…Total cell lysates were size-fractionated on SDS-polyacrylamide gels (Life Technologies) and then analyzed by Western blot analysis as previously described [7, 9, 10]. Antibodies were either from Santacruz Biotechnology [SR-A (sc-20660), CD36 (sc-9154)] or Sigma-Aldrich (β-actin).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Total cell lysates were size-fractionated on SDS-polyacrylamide gels (Life Technologies) and then analyzed by Western blot analysis as previously described [7, 9, 10]. Antibodies were either from Santacruz Biotechnology [SR-A (sc-20660), CD36 (sc-9154)] or Sigma-Aldrich (β-actin).…”
Section: Methodsmentioning
confidence: 99%
“…The process involves actin-dependent ruffling of the plasma membrane and the subsequent fusion of the membrane to itself to form intracellular fluid filled vacuoles 0.5–5 μM in diameter [5, 6]. Although an important role for macropinocytosis in the uptake of native LDL is well established [5, 6], our recent studies have extended the role of this process to the uptake of modified LDL by macrophages [7, 8]. Previous studies have shown that PI3K plays a potentially important role in macropinocytosis, including the uptake of native LDL, under certain conditions [5, 6].…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we demonstrate that oral fish oil supplementation induced a significant increase in have begun to uncover some as-of-yet unclear associations 17,29,[47][48][49] . Akin to our results, one study displayed a 26% decrease in PPARγ mRNA in mouse aortas following a 12 week fish oil diet; in another study TNFα decreased PPARγ synthesis in macrophages 50 , perhaps providing a mechanism for the M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT 13 decreased PPARγ mRNA, unchanged particle phagocytosis and unchanged macrophage vacuolization in this study.…”
Section: Discussionmentioning
confidence: 67%
“…We tested the potential inhibitory effect of BBR on macropinocytosis evaluating the uptake of lucifer yellow (LY) [23] in THP-1 macrophages through confocal microscopy. When cells were in basal conditions, macropinocytosis was clearly detectable after 2 h incubation with LY ( Fig.…”
Section: Effect Of Bbr On Macropinocytosismentioning
confidence: 99%